2008
DOI: 10.1007/s00405-007-0575-7
|View full text |Cite
|
Sign up to set email alerts
|

A review of the current management of impacted foreign bodies in the oesophagus in adults

Abstract: Patients with acute oesophageal obstruction, either due to a foreign body or food bolus, present to any of the specialties of Otorhinolaryngology, General Surgery, Cardiothoracic Surgery or Gastroenterology. To review current routine management of this condition, we conducted a postal survey of all the consultants in the aforementioned specialties in the South Thames region. The aims of the survey were to assess current practice and to produce a standardized management plan for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…1 The majority of ingested foreign bodies resolve spontaneously without causing complications. 2,3 However, it is a potentially serious condition that can result in oesophageal perforation and mediastinitis if left untreated. 4 Most cases of foreign body ingestion occur in the paediatric population (peak incidence 6 months -6 years).…”
Section: Discussionmentioning
confidence: 99%
“…1 The majority of ingested foreign bodies resolve spontaneously without causing complications. 2,3 However, it is a potentially serious condition that can result in oesophageal perforation and mediastinitis if left untreated. 4 Most cases of foreign body ingestion occur in the paediatric population (peak incidence 6 months -6 years).…”
Section: Discussionmentioning
confidence: 99%
“…Longstreth et al [2] and other authors [12,[20][21][22][23] reported that flexible esophagoscopy permitted disimpaction in 98% of cases. The esophageal perforation rates with flexible endoscopy have been reported to be between 0.018 and 0.05% as opposed to between 0.2 and 1.2% using rigid endoscopy [24,25]. In most cases the cause of the Total 54 bolus impaction is unknown at the time of removal.…”
Section: Discussionmentioning
confidence: 99%
“…There is a long list of serious complications as a consequence of esophageal foreign bodies, including perforation, retropharyngeal abscess, mediastinitis, and fistulas [6]. The mortality rates are as high as 50% as a result of subsequent intrathoracic infection [7]. Conservative or surgery are the treatment modalities for mediastinitis.…”
Section: Discussionmentioning
confidence: 99%